Long-term air pollution exposure and Parkinson's disease mortality in a large pooled European cohort: An ELAPSE study. (January 2023) - Cole-Hunter, Thomas; Zhang, Jiawei; So, Rina; Samoli, Evangelia; Liu, Shuo; Chen, Jie; Strak, Maciej; Wolf, Kathrin; Weinmayr, Gudrun; Rodopolou, Sophia; Remfry, Elizabeth; de Hoogh, Kees; et al.
Highlights: We study the association of long-term air pollution exposure with Parkinson's Disease (PD) Our study among 271, 720 ELAPSE cohort participants noted 381 deaths from PD. We find that long-term exposure to PM2.5, NO2 and BC are associated with risk of PD death. Associations persist at low levels of pollutant concentration, below current EU standards. Our study adds strong evidence in support of an association between air pollution and PD. Abstract: Background: The link between exposure to ambient air pollution and mortality from cardiorespiratory diseases is well established, while evidence on neurodegenerative disorders including Parkinson's Disease (PD) remains limited. Objective: We examined the association between long-term exposure to ambient air pollution and PD mortality in seven European cohorts. Methods: Within the project 'Effects of Low-Level Air Pollution: A Study in Europe' (ELAPSE), we pooled data from seven cohorts among six European countries. Annual mean residential concentrations of fine particulate matter (PM2.5 ), nitrogen dioxide (NO2 ), black carbon (BC), and ozone (O3 ), as well as 8 PM2.5 components (copper, iron, potassium, nickel, sulphur, silicon, vanadium, zinc), for 2010 were estimated using Europe-wide hybrid land use regression models. PD mortality was defined as underlying cause of death being either PD, secondary Parkinsonism, or dementia in PD. We applied Cox proportional hazard models to investigate the associations between air pollution and PD mortality, adjusting for potential confounders. Results: Of 271, 720 cohort participants, 381 died from PD during 19.7 years of follow-up. In single-pollutant analyses, we observed positive associations between PD mortality and PM2.5 (hazard ratio per 5 µg/m 3 : 1.25; 95% confidence interval: 1.01–1.55), NO2 (1.13; 0.95–1.34 per 10 µg/m 3 ), and BC (1.12; 0.94–1.34 per 0.5 × 10 -5 m -1 ), and a negative association with O3 (0.74; 0.58–0.94 per 10 µg/m 3 ). Associations of PM2.5, NO2, and BC with PD mortality were linear without apparent lower thresholds. In two-pollutant models, associations with PM2.5 remained robust when adjusted for NO2 (1.24; 0.95–1.62) or BC (1.28; 0.96–1.71), whereas associations with NO2 or BC attenuated to null. O3 associations remained negative, but no longer statistically significant in models with PM2.5 . We detected suggestive positive associations with the potassium component of PM2.5 . Conclusion: Long-term exposure to PM2.5, at levels well below current EU air pollution limit values, may contribute to PD mortality.